Darwin’s Chalcopyrite: Engaging Museum Audiences with Global Extractive Stories - Liz Hide (Museum & Society)
Challenging established narratives and acknowledging the colonial histories of natural history collections is an essential first step in addressing the structural racism that exists within European museums (Das and Lowe 2018). Mineral collections provide a direct link to the extraction and exploitation of natural resources, but mineral displays in museums rarely address the human, economic, and environmental conditions that brought these specimens to the museum, nor their framing within colonial power structures, focusing instead on inherent attractiveness and/or physical and chemical properties. As part of its strategic commitment to addressing this challenge, this paper outlines a case study in the Sedgwick Museum of Earth Sciences, Cambridge, where observations and collections made by Charles Darwin during his three-year voyage around the world on board HMS Beagle provide a window onto wider social and economic issues that continue to be relevant today. The presence of a strong, if one-sided documentary record coupled with a museum’s commitment to sharing alternative narratives can challenge this ‘museal silence’ and enable the museum to address issues of social justice.